In vitro Antagonistic Interactions Between Endophytic Basidiomycetes of Oil Palm (Elaeis guineensis) and Ganoderma boninense. Issue 10 (24th June 2016) - Naidu, Yuvarani; Idris, Abu Seman; Madihah, Ahmad Zairun; Kamarudin, Norman
Abstract: Ganoderma boninense is a white rot basidiomycete that causes basal stem rot disease of oil palm ( Elaeis guineensis ). The aims of this study were to identify endophytic basidiomycetes occurring naturally within oil palm and to assess their potential as biocontrol agents against G. boninense strain PER71 in vitro . In total, 376 isolates were recovered from samples collected from the root, stem and leaves of oil palm using Ganoderma ‐selective medium. Ten of these isolates (2.7% of the total 376 isolates) were identified as basidiomycetes on the basis of clamp connections and the production of poroid basidiomes after incubation in glass jars containing PDA medium for 7–12 days. The isolates were identified using ITS rDNA sequencing as Neonothopanus nambi (five isolates), Schizophyllum commune (four isolates) and Ganoderma orbiforme (one isolate). The N. nambi isolates showed the greatest antagonistic activity against G. boninense, based on 73–85% inhibition of the radial growth measurements of G. boninense in dual culture and 76–100% inhibition of G. boninense growth in a culture filtrate assay. Possible modes of action for the antagonism shown by N. nambi against G. boninense in vitro include competition for substrate availability, space and the production of non‐volatile metabolites or antibiotics that inhibited the growth of G. boninense . Further in vivo investigations are required to determine the ability of N. nambi isolates to colonize oil palm seedlings and to protect oil palm from infection when challenged with G. boninense .